Pengaruh Tipe Mixer Ejektor dan Sudu Non-Twisted Naca 6412 Terhadap Daya Listrik Turbin Angin Poros Horizontal - Wisnu Aristyawan; Danar Susilo Wijayanto; Nugroho Agung Pambudi (Jurnal Mekanika dan Sistem Termal, 2017)
The purpose of this study was to determine the effect of mixer ejector and a non-twisted blade airfoil NACA 6412 toward power output generated in the horizontal axis wind turbine (HAWT). The type of blade used in this experiment is a blunt, rectangular and taper. There are three artificial low wind-speed applied at 2.5 m / s, 3.5 m / s and 4.5 m/s. All the experimental data is carried out by several instruments such as anemometer, tachometer, multitester and recorded by a data logger. The results showed that the blunt wind turbine blade produces the highest power output at 0.43 W at a wind speed of 4.5 m/s with a rotor rotational speed of 183.4 RPM. While, the lowest power output produced by taper blade power output at of 0.07 W at 87.9 rpm at a wind speed of 2.5 m/s. In the experimental of additional of the mixer ejector, diffuser type produces the highest power output at 0.83 W at a wind speed of 4.5 m/s. The power output increased by 93 % compared to an original wind turbine without the addition of mixer ejector at 0.43 W.